2000
DOI: 10.1002/1520-6394(2000)12:1<13::aid-da2>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicide attempts among African American women

Abstract: The aim of this study was to examine psychological and interpersonal risk factors for suicidal behavior in low income, African American women; 285 African American women who reported being in a relationship with a partner in the past year were studied, 148 presented to the hospital following a suicide attempt, and 137 presented for general medical care. Cases were compared to controls with respect to psychological symptoms, alcohol and drug abuse, family violence (intimate partner abuse, childhood trauma), rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 46 publications
4
64
1
Order By: Relevance
“…Black women with experiences of IPV have been found to suffer from adverse mental health outcomes, as documented by cross-sectional studies and the only prospective cohort study. 18,31,50,55 In the recent prospective study, psychological, sexual, and physical IPV were independently associated with depression, suicidality, and PTSD among African American female emergency department patients. 49 Mental health symptoms also increased significantly with the amount of abuse experienced.…”
Section: Mental Healthmentioning
confidence: 99%
“…Black women with experiences of IPV have been found to suffer from adverse mental health outcomes, as documented by cross-sectional studies and the only prospective cohort study. 18,31,50,55 In the recent prospective study, psychological, sexual, and physical IPV were independently associated with depression, suicidality, and PTSD among African American female emergency department patients. 49 Mental health symptoms also increased significantly with the amount of abuse experienced.…”
Section: Mental Healthmentioning
confidence: 99%
“…Several studies have demonstrated an association with IPV and increased levels of mental health symptoms (Coker et al, 2002;Kaslow et al, 2001). Romito, Turan, and De Marchi (2005) reported that compared with nonabused women, women who were currently experiencing IPV were almost 6 times more likely to report psychological distress, and women who had experienced IPV in the past were 3 times more likely to have psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income, African American women experience disproportionately high levels of IPV (Rennison & Planty, 2003) and psychosocial difficulties (West, 2002). One of the most negative sequelae of IPV among low-income African American women is an increased risk for suicidal behavior (Kaslow et al, 1998(Kaslow et al, , 2000Stark & Flitcraft, 1996;Thompson et al, 1999;Thompson, Kaslow, & Kingree, 2002). Women who report a history of IPV are more 1 Georgia State University, Atlanta, Georgia.…”
mentioning
confidence: 99%